LINGUA-DIDACTIC PROBLEMS OF TEACHING FOREIGN LANGUAGES IN THE SYSTEM OF CONTINUOUS EDUCATION. ("Conference on Universal Science Research 2023", 2023)
Lingua-didactic problems of foreign language teaching in system of continuous education( schools, academic lyceums, vocational colleges) Hence the teacher should know exactly what his pupils are expected to achieve in learning his subject, what changes he can bring about in his pupils at the end of the course, at the end of the year, term, month, week and each particular lesson, i.e., he should know the aims and objects in foreign language teaching in schools. Hence the teacher should know exactly what his pupils are expected to achieve in learning his subject, what changes he can bring about in his pupils at the end of the course, at the end of the year, term, month, week and each particular lesson, i.e., he should know the aims and objects in foreign language teaching in schools.